RESPONSIBILITY OF THE WORLD HEALTH ORGANIZATION IN DEALING WITH THE COVID-19 OUTBREAK ACCORDING TO INTERNATIONAL LAW - VIYANI ANNISA PERMATASARI; ABDUL MAASBA MAGASSING; IIN KARITA SAKHARINA (Awang Long Law Review, 2022)
This research aims to analyze WHO's responsibility in overcoming the Covid-19 pandemic according to International Law and analyze the form of international cooperation in overcoming the Covid-19 pandemic. The study uses normative juridical research with statute and case approaches are used in this paper. The legal research materials are international conventions, legal literature, international and national law journals, and legal research materials from the internet. The results showed that WHO in the pandemic era was morally responsible. Through the socialization of health protocols by international standards, campaigning for a healthy lifestyle, good sanitation, and distribution of vaccines. The distribution of vaccines has not been amply enjoyed evenly, especially in developing countries. Some countries are affected by inequality in distributing vaccines by developed countries. Thus, international cooperation between states or a state and World Health Organization (WHO) has not achieved vaccination equality. One country that should be responsible for the losses to countries around the world is Tiongkok, as the origin of the pandemic Covid-19. According to the principles of international law, a sovereign state cannot be put on trial by another state with the same status. Furthermore, the responsibility that can hold for Tiongkok is in the form of an apology statement to the international community and conducting an in-depth investigation of the origin of the Coronavirus first appeared.